Impact of Emotional Intelligence on Big Five Factor Traits of Nepalese College Students - Devakota, Surya Prasad; Khadka, Ajaya Kumar; Neupane, Dipendra Kumar (DEPAN, 2024)
Finding out how the Big Five Personality Traits affected the emotional intelligence of male and female college students was the main goal of the study. 150 people (N=150) participated in the study; they were divided into 75 M and 75 F groups based on their age ranges of 18 to 22, respectively. The intended respondents complete the survey that is distributed via Google Drive. The results showed that, for males, there is no relationship between emotional intelligence and neuroticism, openness to experience, and agreeableness; on the other hand, for females, there is a relationship between emotional intelligence and extraversion, agreeableness, and Conscientiousness, as well as neuroticism and openness to experience. The survey and causal comparative design have been used.The results also showed that there is no discernible difference between male and female college students in terms of neuroticism, extraversion, agreeableness, openness to experience, or emotional intelligence, with the exception of conscientiousness. The study's limitations and effects have been examined and a conclusion has been reached.